PENGARUH PENAMBAHAN CANGKANG KELAPA SAWIT SEBAGAI SUBSTITUSI AGREGAT KASAR TERHADAP KUAT TEKAN BETON - Risky Akbar Yusda; Ellyza Chairina (Universitas Islam Sumatera Utara, 2026)
The growing demand for concrete encourages the use of agricultural waste as eco-friendly materials, one of which is palm oil shells as a substitute for coarse aggregate. This study examined the effect of palm oil shell addition (5% and 7.5%) on concrete compressive strength. Tests on cylindrical specimens at 28 days showed that 5% addition increased strength to 33.24 MPa compared to 32.66 MPa for normal concrete, while 7.5% reduced it to 30.34 MPa. The results indicate that the optimum percentage is 5%, producing concrete with acceptable strength.